Mixing Aβ(1–40) and Aβ(1–42) peptides generates unique amyloid fibrils. Issue 62 (6th July 2020) - Cerofolini, Linda; Ravera, Enrico; Bologna, Sara; Wiglenda, Thomas; Böddrich, Annett; Purfürst, Bettina; Benilova, Iryna; Korsak, Magdalena; Gallo, Gianluca; Rizzo, Domenico; Gonnelli, Leonardo; Fragai, Marco; et al.
Abstract : Solid-state NMR experiments reveal that the two isoforms of the beta-amyloid peptide (Aβ(1–40) and Aβ(1–42)) are able to form unique interlaced mixed fibrils. Abstract : Recent structural studies show distinct morphologies for the fibrils of Aβ(1–42) and Aβ(1–40), which are believed not to co-fibrillize. We describe here a novel, structurally-uniform 1 : 1 mixed fibrillar species, which differs from both pure fibrils. It forms preferentially even when Aβ(1–42) : Aβ(1–40) peptides are mixed in a non-stoichiometric ratio.